Locating Land Use at Neolithic Çatalhöyük, Turkey: The Implications of 87Sr/86Sr Signatures in Plants and Sheep Tooth Sequences. (31st July 2013) - Bogaard, A.; Henton, E.; Evans, J. A.; Twiss, K. C.; Charles, M. P.; Vaiglova, P.; Russell, N.
<x xml:space="preserve">Abstract</x> We evaluate local versus distant land‐use models at Neolithic Çatalhöyük, central Anatolia, using strontium isotope analysis of sheep tooth enamel and charred plant remains. Interpretation of strontium in sheep tooth sequences is constrained by previous oxygen isotope work, which largely excludes summer movement to the mountains but cannot distinguish between herding on the plain and the closest upland‐zone, Neogene limestone terraces. We establish a baseline contrast in modern plant strontium values between the plain and terraces and infer predominant herding on the plain from seven sheep tooth sequences. Archaeobotanical plant strontium values exclude the use of the terraces for cultivation and foraging. Relatively local crop and sheep management, plausibly intensive and integrated to some degree, given limited dry ground, appears likely on the basis of this pilot study.